Central angiotensin II induces sodium bicarbonate intake in the rat - David, Richard B. [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2008)
The aim of this work was to test mineral preference in hydrated rats that received a pulse intracerebroventricular (icv(p)) injection of ANG II at a dipsogenic dose (50 ng). The icv(p) ANG II induced a four-fold higher ingestion of 0.15 M NaHCO(3) than of other mineral solutions at palatable concentrations (0.15 M NaCl, 0.05 mM CaCl(2) and 0.01 M KCl) in a five-bottle test with water available in a fifth bottle; water intake was not consistently high in this test. Contrary to what is predicted by the mineralocorticoid/angiotensin II synergy hypothesis, the 0.15 M NaCl intake in the five-bottle test was not enhanced by icvp ANG H preceded by deoxycorticosterone (DOCA) treatment (2.5 mg/day for 3 days); neither was the NaHCO(3) intake. This result contrasted with the vigorous ingestion of both isotonic sodium solutions, but mostly of NaCl, rather than of other fluids, by sodium-depleted (furosemide 10 mg sc + 24 h removal ambient sodium) rats in a sodium appetite test. The results suggest that mineralocorticoid combined to icv(p) ANG II does not simulate the sodium preference shown during sodium appetite. The results also show that a dipsogenic dose of central ANG II induces a reliable ingestion of isotonic sodium bicarbonate in the rat. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; mineral preference; NaHCO(3) intake; angiotensin II; mineralocorticoid; sodium depletion; synergy